The prevalence of attention-deficit hyperactivity disorder and its associated factors among children in Ethiopia, 2024: a systematic review and meta-analysis - Azmeraw, Molla; Temesgen, Dessie; Kassaw, Amare; Zemariam, Alemu Birara; Kerebeh, Gashaw; Abebe, Gebremeskel Kibret; Alamaw, Addis Wondmagegn; Abate, Biruk Beletew (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Attention-deficit hyperactivity disorder (ADHD) is a neuropsychiatric condition that affects children. Its magnitude varies by area, ranging from 0.2% to 26.8%. Even though there is debate, culture and geographical location may have little or no influence on the epidemiology of ADHD worldwide. Despite this variation, debate over the national prevalence and location of ADHD is unknown in Ethiopia. Therefore, this study aimed to assess the pooled prevalence of ADHD and its contributing factors among children. Methods Electronic databases, including Google Scholar, PubMed, Scopus, EMBASE, Web of Science, ScienceDirect, and institutional repositories, were searched. The studies that covered the prevalence and/or risk factors of ADHD in children were included in the collection. The Joanna Briggs Institute quality rating tool was used to rate the quality of each study. The data were extracted using Microsoft Excel 2019, and the statistical analysis was performed using STATA 17.0. Using a random-effects model, we evaluated the combined prevalence of ADHD and associated factors. The Cochrane Q-test and I2 test statistics were used to quantify the heterogeneity. Furthermore, publication bias was examined using funnel plot graphs and Egger's tests. A Galbraith plot was employed to illustrate outliers. Sensitivity analysis was also applied. Result This study included a total of six articles with 4,338 participants. The pooled prevalence estimate of ADHD was 8.81% [95% confidence interval (CI), 4.52–13.11; I2 = 96.95%; P = 0.001]. Age 6–12 [adjusted odds ratio (AOR) = 3.51 (95% CI, 1.38–5.64), I2 = 0%; P = 0.001], being male [AOR = 1.94 (95% CI, 1.09–2.79), I2 = 0%; P = 0.001], and living with a single parent [AOR = 4.92 (95% CI, 1.24–861), I2 = 0%; P = 0.001] were significant variables. Conclusion and recommendation One out of every 12 children in Ethiopia suffers from ADHD. Living with a single parent, being male, and being between the ages of 6 and 12 were risk factors for ADHD. A nationwide study with a large sample size may be required to ascertain the true impact of ADHD. It may be crucial to improve school health services to identify ADHD early and lessen its long-term effects.